Ambivalence Surrounding Elderly Widows’ Sexuality in Urban Uganda - Nyanzi, Stella (Ageing International, 2011)
The elderly are commonly stereotyped as asexual beings. Alternatively mainly negative images abound about the sexual activities of elderly people. Based on ethnographic data this article explores diverse sexualities of elderly widows and widowers in an urban periphery of Kampala city. Widowhood is socially constructed as an asexual period in this patriarchal society where heteronormativity and marriage prevail as the accepted norms. While widowers are generally encouraged to remarry after observing proprieties of mourning, sexual activity among elderly widows is heavily proscribed against particularly because it is not procreative. Adult children control the sexuality of their elderly parents, often by discouraging sexual liaisons. Adult children may also arrange for new spouses with utilitarian value such as providing healthcare for ill elders. Post-menopausal widows have less sexual appeal than younger widows for whom reproduction is a viable outcome of sexuality. Widowers and younger widows are more likely to remarry than elderly widows. Consequently for some older widows, the cultural institution of widow inheritance provides an opportunity to resume sexual activity, and benefit from the levirate guardian’s support. However other older widows rejected inheritance by levirate guardians because of fears of catching HIV/AIDS. HIV does infect elderly Ugandans, although prevention and care interventions generally exclude targeting the elderly. Loneliness was widespread among elderly widows. Many felt isolated, dislocated from former social circulation and missed being relevant. However there were a few elderly individuals who were actively engaged in providing sexual education, advocating for sexual health promotion, and defending the sexual rights of the younger generations in their immediate environs. There is an urgent need for more research about the realities of elderly people’s sexualities, sexual health and sexual rights particularly in resource-poor contexts.
Keywords: Elderly .Widowhood . Sexuality and ageing . Uganda